Anaerobic co-digestion of catering food waste utilizing Parthenium hysterophorus as co-substrate for biogas production. (May 2019) - Tayyab, Aumbreen; Ahmad, Zulfiqar; Mahmood, Tariq; Khalid, Azeem; Qadeer, Samia; Mahmood, Shahid; Andleeb, Shaista; Anjum, Muzammil
Abstract: Catering food waste is a constant concern both at home and in the restaurant kitchens. Advances in the catering industry are generating a significant amount of catering waste, which poses a significant risk to public health and the environment. The anaerobic digestion technology used to produce biogas from various substrates has attracted worldwide attention for its economics and ease of use. This study evaluated the potential of pretreated parthenium weed (as co-substrate) in anaerobic co-digestion of catering food waste in lab scale bioreactors using different mixing ratios (0:100, 20:80, 60:40, 40:60, 80:20, and 100:0 TS basis) for biogas production. The performance parameters of the bioprocess were evaluated using COD, C/N ratio, solids content, pH and the biogas potential. The results showed that the maximum biogas production rate (559 ml L −1 d −1 ) and accumulative biogas (5532 ml L −1 ) was achieved in the PCP2 co-digestion reactor, where 60% catering food waste and 40% parthenium weed (pre-treated) was used under static incubation at 30 ± 1 °C. Furthermore, in response to pretreatment conditions, a steady decrease in volatile solids (VS), total solids (TS), C/N ratio, and organic content were observed. The highest removal efficiency of organic matter (38.9%) was achieved by the PCP2 co-digestion reactor with a maximum reduction of 79% of iCOD in 60 process days. The present findings suggest the suitability and application of the pretreated parthenium weed as a potential co-substrate for biogas production in the anaerobic digestion of catering food waste. Highlights: Catering waste is generated in excessive quantities and has significant environmental and economic impacts. Anaerobic co-digestion is an effective biological process for treating a wide range of catering waste. Parthenium weed can be used as a potential substrate for anaerobic co-digestion of catering waste in biogas production. The optimal ratio of catering waste to parthenium (60:40) showed optimal biogas in static incubation at 30 °C. The developed reactor had the potential to increase the availability of soluble carbon and subsequently biogas production.